Stable water isotope data for the surface samples collected at the Allan Hills Blue ice area - Introne, Douglas; Kurbatov, Andrei V.; Mayewski, Paul A.; Yan, Yuzhen (IEDA: US Antarctic Program Data Center, 2018)
Abstract: Stable water isotope data for the surface ice samples (listed as point numbers coordinates provided) collected at the Allan Hills Blue ice area have been generated under a collaborative effort by the University of Maine Climate Change Institute (NSF Award#1443306) and Princeton University (NSF Award# 1443263). This data set contains stable isotope data (dD, d18O) of meltwater samples collected from the area(76.73165 to 76.73348 S, 159.35343 to 159.42112 E).